2019
DOI: 10.24272/j.issn.2095-8137.2019.030
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte cell-derived chemotaxin 2 inhibits development of atherosclerosis in mice

Abstract: Leukocyte cell-derived chemotaxin 2 (LECT2), a multifunctional hepatokine, is involved in many pathological conditions. However, its role in atherosclerosis remains undefined. In this study, we administered vehicle or LECT2 to male Apoe -/- mice fed a Western diet for 15 weeks. Atherosclerotic lesions were visualized and quantified with Oil-red O and hematoxylin staining. The mRNA expression levels of MCP-1, MMP-1, IL-8, IL-1β, and TNF-α were analyzed by quantitative real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…IL-8 is another widely studied gene that is relevant to atherogenesis. In atherosclerosis, ox-LDL induces the overexpression of IL-8 by the vascular endothelial cells, which could activate macrophages and aggravate inflammatory responses [40]. Our study showed that NORADknockdown increased the IL-8 levels in ox-LDLtreated HUVECs.…”
Section: Agingmentioning
confidence: 52%
“…IL-8 is another widely studied gene that is relevant to atherogenesis. In atherosclerosis, ox-LDL induces the overexpression of IL-8 by the vascular endothelial cells, which could activate macrophages and aggravate inflammatory responses [40]. Our study showed that NORADknockdown increased the IL-8 levels in ox-LDLtreated HUVECs.…”
Section: Agingmentioning
confidence: 52%
“…Additionally, the relationships between the levels of serum LECT2 and eosinophil levels of AD patients (eosinophil In recent years, studies have been focused on the relationships between LECT2 and inflammatory diseases. (13). Furthermore, Tanisawa et al reported that participants with dyslipidemia had higher levels of plasma LECT2 than those without dyslipidemia (17).…”
Section: Serum Lect2 Were Related With Eosinophil Levels Of Ad Patientsmentioning
confidence: 99%
“…We believe that LECT2 may cause the occurrence of AD in many ways. LECT2 is associated with many inflammation-linked signaling pathways such as NF-κB and STAT1, among others (12,13,15). NF-κB is an important transcriptional regulator that modulates the immune and inflammatory responses involved in the transcription of several targets (24).…”
Section: Serum Lect2 Were Related With Eosinophil Levels Of Ad Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were incubated in diaminobenzidine until a change in color was observed under the microscope and then the nucleus was stained with hematoxylin. 22 Immuno uorescence staining procedure was similar to immunostaining.…”
Section: Histology and Immunostainingmentioning
confidence: 99%